\(a) M(x)=2-5x^2+3x^4-4x^2+3x+x^4-4x^6-7x\\ =2+(-5x^2-4x^2)+(3x^4+x^4)+(3x-7x)-4x^6\\ =2-9x^2+4x^4-4x-4x^6\\ =-4x^6+4x^4-9x^2-4x+2\\ N(x)=-1+5x^6-6x^2-5-9x^6+4x^4-3x^2\\ =(-1-5)+(5x^6-9x^6)+(-6x^2-3x^2)+4x^4\\ =-6-4x^6-9x^2+4x^4\\ =-4x^6+4x^4-8x^2-6\\ b)H(x)=M(x)+N(x)\\ =-4x^6+4x^4-9x^2-4x+2+(-4x^6+4x^4-8x^2-6)\\ =-4x^6+4x^4-9x^2-4x+2-4x^6+4x^4-8x^2-6\\ =(-4x^6-4x^6)+(4x^4+4x^4)+(-9x^2-8x^2)-4x+(2-6)\\ =-8x^6+8x^4-17x^2-4x-4\\\)
\(G(x)=M(x)-N(x)\\ =-4x^6+4x^4-9x^2-4x+2-(-4x^6+4x^4-8x^2-6)\\ =-4x^6+4x^4-9x^2-4x+2+4x^6-4x^4+8x^2+6\\ =(-4x^6+4x^6)+(4x^4-4x^4)+(-9x^2+8x)-4x+(2+6)\\ =-x^2-4x+8\)